Answers

2014-02-18T20:01:09+05:30
Let f = father's age
Let s = son's age
Given that the present age of the father is three times the age of his son
Therefore, f = 3s + 3
Given that after 3 years father's age will be 10y more twice the age of his son
f + 3 = 2(s + 3) + 10
f + 3 = 2s + 6 + 10
f + 3 = 2s + 16
f = 2s + 16 - 3
f = 2s + 13
Determine there ages:
Substitute (3s + 3) for f in the above equation, find s
3s + 3 = 2s + 13
3s - 2s = 13 - 3
S = 10 YEARS, son's present age =
f = 3 x 10 + 3
f = 33 years
Therefore, father's present age is
33 + 3 = 2(10 + 3) + 10
36 = 2(13) + 10
Now solve ahead :)

1 5 1
2014-02-19T13:39:00+05:30
Let the present ages of father is x and of son is y.
x = 3y + 3 , (x+3) = 10 + 2(y + 3)
3y + 6 = 10 + 2y + 6
y = 10 , x=33

0